2011
DOI: 10.1093/hmg/ddr587
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association and gene–environment interaction study for serum triglycerides levels in a healthy Chinese male population

Abstract: Triglyceride (TG) is a complex phenotype influenced by both genetic and environmental factors. Recent genome-wide association studies (GWAS) have identified genes or loci affecting lipid levels; however, such studies in Chinese populations are limited. A two-stage GWAS were conducted to identify genetic variants that were associated with TG in a Chinese population of 3495 men. Gene-environment interactions on serum TG levels were further investigated for the seven single nucleotide polymorphisms (SNPs) that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 22 publications
3
59
0
Order By: Relevance
“…18 www.nature.com/gene between the two stages in age distribution (37.54 versus 37.31 years, P ¼ 0.54), body mass index (23.31 versus 23.46 kg m À 2 , P ¼ 0.18) and smoking behavior (P ¼ 0.66), excepting for alcohol consumption (P ¼ 0.02). According to the results of independent samples t-test (Table 1), we found that there were significant differences on serum IgG level between drinkers and non-drinkers in the first stage (Po0.001), whereas no significant difference was detected in the second stage (P ¼ 0.158).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…18 www.nature.com/gene between the two stages in age distribution (37.54 versus 37.31 years, P ¼ 0.54), body mass index (23.31 versus 23.46 kg m À 2 , P ¼ 0.18) and smoking behavior (P ¼ 0.66), excepting for alcohol consumption (P ¼ 0.02). According to the results of independent samples t-test (Table 1), we found that there were significant differences on serum IgG level between drinkers and non-drinkers in the first stage (Po0.001), whereas no significant difference was detected in the second stage (P ¼ 0.158).…”
Section: Resultsmentioning
confidence: 99%
“…18 Briefly, about 10 ml overnight fasting venous blood specimens were collected between 0800 and 1100 h in the morning and were transported frozen to the testing center of Department of Clinical Laboratory at the First Affiliated Hospital of Guangxi Medical University in Nanning in two hours, which were centrifuged within 15 to 25 min and stored at À 80 until analysis. IgG was measured with electrochemiluminescence immunoassay on COBAS 6000 system E601 (Elecsys module) immunoassay analyzer (Roche Diagnostics, GmbH, Mannheim, Germany) with the same batch of reagents, and the inter-assay coefficient of variation was 4.97%.…”
Section: Measurement Of Iggmentioning
confidence: 99%
See 3 more Smart Citations